On Emerson’s Poem The Sphinx from the Perspective of Humanism - Zheng, Peiwei; Jingling, Zhang (International Journal of English Literature and Social Sciences (IJELS), 2019)
The Sphinx was one of Emerson’s most enigmatic poems, in which Emerson presented questions in voices of the Sphinx and the great mother, and the poet’s response to the questions. This article was a tentative study of the poem in terms of its meaning by analyzing the images of the Sphinx, the great mother and the poet from the perspective of Humanism.